2021
DOI: 10.47162/rjme.62.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Morphological aspects of the vasculogenesis and angiogenesis during prenatal edification of the circle of Willis: a review

Abstract: Morphological aspects of the vasculogenesis and angiogenesis during prenatal edification of the circle of Willis: a reviewANA MARIA DUMITRESCU 1) , CLAUDIA FLORIDA COSTEA 2,3) , CRISTINA FURNICĂ 4) , MIHAELA DANA TURLIUC 5,6) , ANDREI IONUŢ CUCU 6) , CAMELIA MARGARETA BOGDĂNICI 2,7) , ŞERBAN TURLIUC 8) , GABRIELA FLORENŢA DUMITRESCU 9) , ANCA SAVA 4,9)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
3
0
7
Order By: Relevance
“…In agreement with this concept, the mean of the MVD in this study was significantly high in early stages with tumor size T1 or T2, both inside and outside the tumor, but no correlation was detected when the tumor was in T3 or T4 and when there was LN involvement. A number of authors demonstrated no connection between the MVD value and the clinicopathological factors [18,22,27], nevertheless, many others have shown a strong association between the two [23,28]. This study showed that the percentage of patients with high tumor budding was more than those with intermediate and low tumor budding.…”
Section: Discussionmentioning
confidence: 63%
“…In agreement with this concept, the mean of the MVD in this study was significantly high in early stages with tumor size T1 or T2, both inside and outside the tumor, but no correlation was detected when the tumor was in T3 or T4 and when there was LN involvement. A number of authors demonstrated no connection between the MVD value and the clinicopathological factors [18,22,27], nevertheless, many others have shown a strong association between the two [23,28]. This study showed that the percentage of patients with high tumor budding was more than those with intermediate and low tumor budding.…”
Section: Discussionmentioning
confidence: 63%
“…Type 14 (hypoplastic A1 segment of ACA and hypoplastic contralateral PComA) was within the same values reported by the above authors, but type 18 (bilateral hypoplastic PComAs and bilateral hypoplastic A1 segments of ACAs) was identified in much lower percentage than in the other published series (Table 4 ). Also, in our series, we identified a much higher percentage of other new configurations which can be the results of some changing in the microenvironment during the embryogenesis [ 50 ], may be due to some particular living conditions of the population in this region of our country.…”
Section: Discussionmentioning
confidence: 98%
“…El desarrollo del sistema circulatorio para el suministro de sangre al futuro cerebro comienza con la formación de los seis pares de arterias de los arcos faríngeos primitivos en la etapa embrionaria de 1.3 mm, que posteriormente se someten a cambios durante el desarrollo embrionario (8). Las arterias de los arcos faríngeos se conocen como arcos aórticos, y se denominan del primero al sexto arco aórtico.…”
Section: Embriología Del Polígono De Willisunclassified
“…A partir del tercer arco aórtico se originan las arterias carótidas comunes y las porciones proximales de las arterias carótidas internas. Las porciones distales de las arterias carótidas internas derivan de las extensiones craneales de las aortas dorsales derecha e izquierda (8). Alrededor del día 28 de desarrollo embrionario, la arteria carótida interna se ramifica en la división anterior y posterior.…”
Section: Embriología Del Polígono De Willisunclassified